Introduction to the translation of the Holy Quran | مدخل إلى ترجمة القرآن الكريم - Muhammad Masrur Irsyadi (Al-Zahra : Journal for Islamic and Arabic Studies, 2017)
The purpose of this research is to learn about translation in general, knowledgeof the translation rule and the reasons for the mistake of understanding theQur'an by means of translation, and to identify the appropriate method fortranslating the verses of jihad in the Holy Quran